Impact of digoxin and sodium valproate on the mechanisms of neuroinflammation and neuroapoptosis under experimental epileptogenesis - Tsyvunin , V.V.; Shtrygol’, S.Yu.; Lytkin, D.V.; Shtrygol’ , D.V. (Medicni Perspektivi, 2025)
Cardiac glycoside digoxin may be an effective adjuvant to classical antiepileptic drugs (AEDs) in the drug-resistant epilepsy treatment. However, the mechanisms of digoxin’s anticonvulsant effect, in particular ability of digoxin itself and its combination with classical AED sodium valproate to influence neuroinflammation as well as counteracting neuronal damage, remains unexplored. Thus, the aim of the study is to elucidate the role of individual markers of neuroinflammation and neuronal apoptosis, in particular interleukin-6 (IL-6), tumor necrosis factor α (TNF-α), interleukin-4 (IL-4), Fas ligand (FasL), heat shock protein 70 (HSP70), 5-lipoxygenase (5-LOX) and nitric oxide synthase (NOS) in the realization of the anticonvulsant potential of digoxin and sodium valproate under experimental epileptogenesis. The model of chronic epileptogenesis, kindling induced pentylenetetrazole (PTZ) in mice, has been used. 40 animals were divided into 5 groups of 8 mice each: vehicle control (receiving solvent – water), positive control (receiving only PTZ), sodium valproate (150 mg/kg intragastrically), digoxin (0.8 mg/kg subcutaneously), and valproate+digoxin combination. Medicines – both per se and in combination – were administered 30 min before PTZ (30 mg/kg intraperitoneally). After 16 days, IL-6, TNF-α, IL-4, FasL, HSP70, 5-LOX and NOS have been identified in the whole brain. It was confirmed that the combination of digoxin with sodium valproate more effectively prevents the development of seizures than monotherapy. It was proven that sodium valproate and digoxin exhibit pronounced anti-inflammatory properties, restoring the content of TNF-α (but not IL-6) and increasing the expression of IL-4, and in combination they also normalize the level of 5-LOX in the brain. Also, digoxin more clearly than sodium valproate counteracts neuroapoptosis and neurodegeneration by affecting FasL and HSP70. Cerebral NOS, however, is not involved in the development of experimental seizures, nor in the anticonvulsant effect of sodium valproate and digoxin. The obtained results expand the understanding of the mechanisms of anticonvulsant action of digoxin and sodium valproate and may be important in the development of new strategies for drug-resistant epilepsy treatment.